HUBUNGAN PRE-MENOPAUSE DENGAN KEJADIAN HIERTENSI PADA WANITA DI RT 11 RW 05 KELURAHAN BANJARBENDO SIDOARJO - Farida Umamah; Aprillia Lestari (Jurnal Ilmiah Kesehatan, 2016)
The relationship between pre-menopause women with incidence of hypertension in RT 11 RW 05 Banjarbendo village Sidoarjo. Menopause women have increasing blood pressure is higher than pre-menopause women, it caused by decreasing of hormonal levels. Initial data showed in February 2015 in RT 11 RW 05 Banjarbendo village was obtained 6 out of 10 women or 60% women had symptoms of hypertension in pre- menopause women. The purpose of this study is to analyze the relationship between pre- menopause women with incidence of hypertension in RT 11 RW 05 Banjarbendo village Sidoarjo.It use analytic design, with cross sectional approach. The population were 61 women. The sample were 52 respondents taken by simple random sampling technique. The independent variable was the incidence of hypertension and the dependent variable was the incidence of pre-menopause. Data were collected by using check list. Analyzed by chi square test ( α = 0.05 ) . Study results showed almost all pre–menopause women and most women them had hypertension. Results test ρ = 0.001 < α = 0.05. so H0 is rejected and H1 is accepted . The conclusion of this study is there is relationship between Pre-menopause with incidence of hypertension In women In RT 11 RW 05 Banjarbendo village Sidoarjo. Suggested for women to understand and have knowledge about the signs of pre-menopause and the incidence of hypertension and Health staff to provide information to the women about the signs of pre-menopause and hypertension .